Prevalence of anti-lymphocyte IgM autoantibodies driving complement activation in COVID-19 patients - Pérez-Díez, Ainhoa; Liu, Xiangdong; Calderon, Stephanie; Bennett, Ashlynn; Lisco, Andrea; Kellog, Anela; Galindo, Frances; Memoli, Matthew J.; Rocco, Joseph M.; Epling, Brian P.; Laidlaw, Elizabeth; Sneller, Mike C.; et al. (Frontiers in Immunology, 2024)
Introduction COVID-19 patients can develop autoantibodies against a variety of secreted and membrane proteins, including some expressed on lymphocytes. However, it is unclear what proportion of patients might develop anti-lymphocyte antibodies (ALAb) and what functional relevance they might have. Methods We evaluated the presence and lytic function of ALAb in the sera of a cohort of 85 COVID-19 patients (68 unvaccinated and 17 vaccinated) assigned to mild (N=63), or moderate/severe disease (N=22) groups. Thirty-seven patients were followed-up after recovery. We also analyzed in vivo complement deposition on COVID-19 patients’ lymphocytes and examined its correlation with lymphocyte numbers during acute disease. Results Compared with healthy donors (HD), patients had an increased prevalence of IgM ALAb, which was significantly higher in moderate/severe disease patients and persisted after recovery. Sera from IgM ALAb+ patients exhibited complement-dependent cytotoxicity (CDC) against HD lymphocytes. Complement protein C3b deposition on patients’ CD4 T cells was inversely correlated with CD4 T cell numbers. This correlation was stronger in moderate/severe disease patients. Discussion IgM ALAb and complement activation against lymphocytes may contribute to the acute lymphopenia observed in COVID-19 patients.